Disenchanted : the trials of Cinderella - Morrison, Megan, 1976- (Morrison, Megan, 1976- Tyme, 2019)
Reimagining of the classic fairy tale "Cinderella." Ella Coach hopes for revolution after her mother dies working in a sweatshop, and Prince Dash Charming hopes to reverse a curse that has made the rest of his family liars and cheaters. When Serge, an executive fairy godfather, sees Ella's name come up on his list, it might just be possible for Ella and Dash to change their world for the better.